Frequency of Micro Albuminuria in Diabetic patients at the Diabetic Clinic of Bahawal Victoria Hospital Bahawalpur - Malik, Jalil Iqbal; Azhar, Munir Ahmad; Channar, Muhammad Saleem; Shah, Aftab Hassan; Khan, Muhammad Akbar (Annals of King Edward Medical University, 2018)
Study was carried out to determine the prevalence of Microalbuminurea in patients suffering from Diabetes Mellitus type-II. Attending the "diabetic clinic" at the medical outpatient department of Bahawal Victoria Hospital from May 2003 to September 2003. Three hundred diagnosed cases of diabetes mellitus on oral hypoglycemic agents with ages between 40-60 years, irrespective of their six, were included in the study. Patients having fever, Urinary Tract Infections, hypertension, heart failure, known renal parenchyma diseases and connective tissue diseases like SLE, RA etc. involving the kidney were excluded from the present study. The study population was, evaluated for albuminuria. They were first screened for Microalbuminurea. Eighteen patients had Macroalbuminurea. They were not followed up further. Of the remaining, 282 patients, 43 (28 males and 15 females) were found to have Microalbuminuria. Overall frequency of Microalbuminuria was 14.34%. Very few studies have so far been conducted to determine the prevalence of Microalbuminuria in Pakistan. Microalbuminuria is considered to be a marker of the earlier & reversible stage of nephropathy. Therefore these patients wire advised to modify their life style. ACE inhibitors were prescribed to such patients to prevent progression of renal disease.